The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1097/bpb.0000000000001087
|View full text |Cite
|
Sign up to set email alerts
|

Use of lateral-exit crossed-pin fixation for pediatric supracondylar humeral fractures: a retrospective case series

Abstract: Surgeons have been reluctant to perform crossed-pin fixation for displaced pediatric supracondylar humeral (SCH) fractures because it carries a risk of iatrogenic ulnar nerve injury. This study aimed to introduce lateralexit crossed-pin fixation for displaced pediatric SCH fractures and to evaluate its clinical and radiological outcomes, with a particular focus on iatrogenic ulnar nerve injuries. Children who underwent lateral-exit crossed-pin fixation for displaced SCH fractures between 2010 and 2015 were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Yun et al [1] reported a radial nerve injury incidence of 1.2%, which is by far higher than that reported by Babal et al [3] of 0.12% for crossed-pin-and 0.63% for lateral-pin fixation.…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…Yun et al [1] reported a radial nerve injury incidence of 1.2%, which is by far higher than that reported by Babal et al [3] of 0.12% for crossed-pin-and 0.63% for lateral-pin fixation.…”
mentioning
confidence: 69%
“…We read with interest the publication by Yun and colleagues [1]. Yun et al [1] stated that surgeons have been reluctant to perform crossed-pin fixation for displaced pediatric supracondylar humeral fractures (SCH), but this is not supported by Pavone et al's [2] recent European survey.…”
mentioning
confidence: 99%
See 3 more Smart Citations